2022
DOI: 10.1021/acs.joc.2c00803
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkyl Carbamoylimidazoles as Isocyanate Equivalents: Exploration of the Reaction Scope for the Synthesis of Ureas, Hydantoins, Carbamates, Thiocarbamates, and Oxazolidinones

Abstract: The reaction of the HCl or trifluoroacetic acid salts of primary amines with carbonyldiimidazole (CDI) is shown to be a preparatively useful method for forming monosubstituted carbamoylimidazoles (28 examples) without the formation of symmetrical urea side products. The utility of these air-and water-stable crystalline carbamoylimidazole reagents was demonstrated by their reactions as blocked or masked isocyanate equivalents. Reaction with various classes of nucleophiles provides access to useful functional gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Similar results were obtained when increasing the milling frequency from 25 to 30 Hz (Table 2, entries 3 and 4). The group of Batey reported that, for primary aliphatic amines, using the hydrochloride form instead of the free amine allowed to suppress the formation of symmetrical urea [16a] . However, in our case, the use of aniline hydrochloride in solvent‐free conditions resulted in a larger proportion of urea (Table 2, entries 5 and 6).…”
Section: Resultsmentioning
confidence: 60%
“…Similar results were obtained when increasing the milling frequency from 25 to 30 Hz (Table 2, entries 3 and 4). The group of Batey reported that, for primary aliphatic amines, using the hydrochloride form instead of the free amine allowed to suppress the formation of symmetrical urea [16a] . However, in our case, the use of aniline hydrochloride in solvent‐free conditions resulted in a larger proportion of urea (Table 2, entries 5 and 6).…”
Section: Resultsmentioning
confidence: 60%
“…The transacylation activity of imidazolides or carbonyl diimidazolides has been extensively investigated by previous researchers. ,, Following this, our upcycling study aimed to explore the reactivity of TBIs in aminolysis reactions with excess n -butylamine under reflux. It was observed that all three TBIs (1b, 2b, and 3b) exhibited sufficient reactivity to form the symmetric 2° terephthalamide (compound c) in Scheme a, with moderate to high yields, as the imidazoles were displaced in favor of amide formation with amines.…”
Section: Resultsmentioning
confidence: 99%
“…The target compounds 3 and 4 were readily synthesized from ethylene glycol diazirine 6 in one step, as illustrated in Scheme . To achieve a rapid and clean protein immobilization in subsequent steps, efficient electrophilic groups on linkers have been selected: imidazole carbamate , and benzyl bromide, where the latter has been widely used for polymer grafting and small molecular functionalization, and the former is known to react efficiently with amine-containing nucleophiles.…”
Section: Resultsmentioning
confidence: 99%